2018
DOI: 10.2214/ajr.17.18489
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic-MRI Correlation After Percutaneous Sampling of Targeted Breast Ultrasound Lesions: Initial Experiences With Limited-Sequence Unenhanced MRI for Postprocedural Clip Localization

Abstract: In our initial experiences with MRI performed for postprocedural clip verification, 26% of presumed correlates to suspicious lesions detected on MRI were not the actual correlate, and 10% of these discordant cases ultimately revealed malignancy. Radiologists should take caution presuming that lesions identified on ultrasound actually represent the suspicious lesions detected on MRI. MRI for clip verification may be useful if ultrasound-guided sampling is pursued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…[23][24][25] Using this technique, Lee et al found an additional malignancy in 1 of 10 discordant cases where MRI showed the clip was not at the expected location following ultrasoundguided biopsy. 19 In the current study, marker clips were used when the target lesion was relatively subtle and could be challenging for subsequent pre-operative localisation or there was uncertainty about the verity of a sonographic correlate (Figs 2 and 5).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…[23][24][25] Using this technique, Lee et al found an additional malignancy in 1 of 10 discordant cases where MRI showed the clip was not at the expected location following ultrasoundguided biopsy. 19 In the current study, marker clips were used when the target lesion was relatively subtle and could be challenging for subsequent pre-operative localisation or there was uncertainty about the verity of a sonographic correlate (Figs 2 and 5).…”
Section: Discussionmentioning
confidence: 94%
“…Use of a limited non‐contrast MRI examination after insertion of a suitable marker clip can be very helpful, particularly when there is pathologic discordance after biopsy of an apparent sonographic correlate 23–25 . Using this technique, Lee et al found an additional malignancy in 1 of 10 discordant cases where MRI showed the clip was not at the expected location following ultrasound‐guided biopsy 19 . In the current study, marker clips were used when the target lesion was relatively subtle and could be challenging for subsequent pre‐operative localisation or there was uncertainty about the verity of a sonographic correlate (Figs 2 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But the presumed correlate depicted on the ultrasound image does not truly represent the lesion noted on MRI [34]. Amie Y. Lee et al [35] found that the presumed sonographic correlate was not the true correlate in 26% of 38 cases and that subsequent MRIguided biopsy of the actual lesion detected on MRI revealed one malignancy in discordant cases. These related researches prove the necessity of the MRIguided intervention.…”
Section: Main Technical Issues Of Mri-guided Detection and Therapeutimentioning
confidence: 99%